Serum Biochemical Constituents in Repeat Breeder vis-a-vis Normal Cyclic Crossbred Cows - Bhardwaz, Anavil; Khajuria, Pallavi; Khatti, Amit; Saini, Gitesh (The Indian Journal of Animal Reproduction, 2026)
The present study was conducted to evaluate and compare serum biochemical constituents in normal cyclic and repeat breeder crossbred cows. A total of 18 animals were selected and categorized into two groups: group I (normal cyclic, n=9) and group II (repeat breeder, n=9). Blood samples were collected, and serum was analysed for total protein, glucose, cal cium, and phosphorus concentrations. The findings revealed that repeat breeder cows exhibited significantly lower levels of serum total protein, glucose, and phosphorus compared to normal cyclic cows. However, no significant difference in serum calcium levels was observed between the two groups. These results suggest that alterations in specific biochemical parameters may contribute to the repeat breeding condition and highlighted the importance of monitoring metabolic status in reproductive management of dairy cattle.
Keywords: Crossbred Cows; Repeat Breeder; Total Protein; Glucose